Power scaling of a narrowband-seeded, non-resonant optical parametric oscillator based on periodically poled LiNbO - Temel,T; Das,S; Spindler,G; Schirrmacher,A; Murray,RT; Piotrowski,M; Wang,L; Chen,W; Petrov,V (Photonics, 2025)
A periodically poled LiNbO3 (PPLN) non-resonant optical parametric oscillator injectionseeded by narrowband sub-50-mW CW radiation at the signal wavelength produces a >3 W average idler power at 2376 nm for a 20 kHz repetition rate, with a ~2 nm spectral linewidth. Seed levels as low as 5 mW are sufficient to produce the desired spectral narrowing effect, and spectral tuning is possible by changing the seed wavelength and simultaneously adjusting the crystal temperature. The spectral features are in good agreement with numerical simulations based on the plane wave approximation.